The SBR start-up performing simultaneous removal of organics, nitrogen and phosphorus from aniline wastewater: Pollutant removal efficiency and microbial community succession. Issue 1 (1st January 2021) - Yang, Mo; Ma, Fang; Xie, Yijia; Li, Lu; Xue, Yingwen
ABSTRACT: Aniline is a toxic organic pollutant and raw material in industries. In this study, the start-up of sequencing batch reactor for treating aniline wastewater was assessed and functional microbial clusters were analyzed after enrichment of denitrifying phosphate-accumulating organisms (DNPAOs). The aniline degradation and subsequent removal of NH4 + -N mainly happened in aerobic condition, and denitrification was conducted in both anaerobic and anoxic conditions. Besides aerobic phosphorus uptake, phosphorus accumulation also occurred via DNPAOs in anoxic condition utilizing nitrate as electron acceptor. The removal efficiencies of COD, NH4 + -N, TN, and TP was over 91.6, 67.1, 65.0, and 79.9% respectively. Proteobacteria, Bacteroidetes, and Firmicutes were found to be predominant at phylum level treating aniline wastewater. Blastocatella, Ferruginibacter and Clostridium were predominant strains involved in aniline degradation and Pseudomonas was enriched in the presence of aniline. Aeromonas, Acinetobacter, and Comamonas may play key roles in nitrogen removal and phosphorus accumulation with tolerance of aniline.